2022
DOI: 10.1002/cne.25307
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ontology of the parabrachial nucleus

Abstract: Diverse neurons in the parabrachial nucleus (PB) communicate with widespread brain regions. Despite evidence linking them to a variety of homeostatic functions, it remains difficult to determine which PB neurons influence which functions because their subpopulations intermingle extensively. An improved framework for identifying these intermingled subpopulations would help advance our understanding of neural circuit functions linked to this region. Here, we present the foundation of a developmental‐genetic onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 226 publications
(407 reference statements)
4
45
0
Order By: Relevance
“…Rostral glutamatergic KF neurons express FoxP2 (Forkhead box protein P2 ) (Geerling et al ., 2017; Karthik et al ., 2022), whereas MOR-expressing glutamatergic neurons in the lateral parabrachial area that project to the forebrain express Calca, a gene that encodes the neuropeptide calcitonin gene-related peptide (CGRP) (Huang et al ., 2021). Considering this, we performed immunohistochemistry for FoxP2 and CGRP on Oprm1+ KF neurons projecting to the ventrolateral medulla.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rostral glutamatergic KF neurons express FoxP2 (Forkhead box protein P2 ) (Geerling et al ., 2017; Karthik et al ., 2022), whereas MOR-expressing glutamatergic neurons in the lateral parabrachial area that project to the forebrain express Calca, a gene that encodes the neuropeptide calcitonin gene-related peptide (CGRP) (Huang et al ., 2021). Considering this, we performed immunohistochemistry for FoxP2 and CGRP on Oprm1+ KF neurons projecting to the ventrolateral medulla.…”
Section: Resultsmentioning
confidence: 99%
“…We found that MOR-expressing dorsolateral pontine neurons that project to the ventrolateral medulla are distinct from CGRP-expressing neurons (Figure 6), although a small population of CGRP-expressing, ventrolateral medulla projecting neurons have been reported (Huang et al ., 2021). Instead, the ventrolateral medulla projecting dorsolateral pontine neurons expressed FoxP2 (Figure 6), and may constitute the population of glutamatergic FoxP2 and Lmx1b neurons recently described in the rostral KF (Karthik et al ., 2022).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the mouse, its distribution throughout the brain has been analyzed (Huang et al 2013). Functionally, among others, it has been implicated in the development of the neocortex in both intracortical (through the corpus callosum) and subcortical projection neurons (Alcamo et al 2008;Britanova et al 2008;Leone et al 2015;McKenna et al 2015), the regionalization of the retrosplenial cortex (Zhang et al 2020), the development of different hypothalamic subpopulations (Kurrasch et al 2007;Blackshaw et al 2010;Bedont et al 2015;Ferran et al 2015;Glendining et al 2020), in particular in the speci cation of dopaminergic neurons in the arcuate nucleus of the hypothalamus (Zhang et al 2021), and recently it has been implicated in the function of the parabrachial area (Fu et al 2019;Jarvie et al 2021;Karthik et al 2022).…”
Section: Introductionmentioning
confidence: 99%